Program Adiwiyata sebagai Wahana dalam Pembentukan Sikap Emati Siswa di Madrasah - Indah Inayati; Rizqiyah Ratu Balqis (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2026)
Empathetic attitude is an important part of students' social-emotional development that needs to be cultivated from the elementary education level, particularly at Madrasah Ibtidaiyah. However, the habituation of empathy values through environment-based school programs has rarely been studied in depth. This research aims to describe the characteristics of the Adiwiyata Program implementation, examine the process of forming students' empathetic attitudes through the program, and analyze the impacts and obstacles that arise in its implementation at MI Assunniyyah 45 Paseban. This research uses a descriptive qualitative approach with data collection techniques consisting of observation, interviews, and documentation. Research subjects were selected using purposive sampling technique, including the madrasah principal, teachers, and students directly involved in the Adiwiyata Program. The results show that the Adiwiyata Program not only functions as an environmental program, but also as a vehicle for shaping students' empathetic attitudes through routine habituation, teacher role modeling, active student involvement, and positive reinforcement. Its impact is evident in changes in students' social behavior, becoming more caring, cooperative, and responsible, although the consistency of empathetic attitudes outside of school supervision remains a challenge that requires continuous reinforcement between schools and families.